Protective effect of grape seed and skin extract on high dosage garlic-induced renal oxidative stress - Sonia Hamlaoui; Oumayma Samti; Meherzia Mokni; Nadia Limam; Alice Carrier; Ferid Limam; Mohamed Amri; Ezzedine Aouani; Lamjed Marzouki (Bangladesh Pharmacological Society, 2012)
In this study, the protective role of grape seed and skin extract (GSSE) against high garlic dose-induced renal toxicity has been evaluated. Rats were intraperitoneally injected with garlic (5 g/kg bw) or GSSE (500 mg/kg bw) or a combination of garlic and GSSE at the same doses daily for one month. Renal oxidative stress markers and antioxidant status were evaluated. We also measured plasma creatinine and urea. Data showed that high garlic dose induced renal toxicity by increasing creatinine and urea and a pro-oxidative status characterized by increased malondialdehyde, carbonyl protein, calcium and H2O2, but decreased free iron. Unexpectedly garlic increased catalase but decreased peroxidase and superoxide dismutase activities. GSSE co-treatment counteracted almost all garlic-induced deleterious effects. In conclusion, high garlic dose induced a pro-oxidative state characterized by the Fenton reaction between H2O2 and free iron, inducing Ca2+ depletion, while GSSE exerted antioxidant properties and Ca2+ repletion.